Upaya Meningkatkan Harga Diri Dengan Kegiatan Positif Pada Pasien Harga Diri Rendah - , Meryana; Widodo, Arif Widodo, A.Kep.,M.Kes (2017)
Background: The concept itself is a negative feeling toward himself, lost confidence, and feel failed to achieve the desire. Low self esteem is feelingthat is not able to achieve the ideal of self evaluation on yourself or abilities. The prevalence of patients with low self esteem in RSJD Arif Zainudin Surakarta in 2016 2520 patients and 334 patients in January 2017. Objective: The authors can understand the nursing care of patients with a diagnosis of self concept low self esteem in the wards Arif Zainudin Surakarta Method: The method used a descriptive case study approach, is to perform nursing care a low self esteem clients ranging from assesment. Intervention, implementation, and evaluation nursing. Result: After the nursing care during 3x24 hours on client with low self esteem issue is resolved partially and intervention should be continued. Conclusion: The problem is resolved partially, thus requiring farther treatment and cooperation with the medical team other, client and families that are indispensable to the success of nursing care. The influence of therapeutic communication therapy to increase its positive abilities, clients before and after the intervention recommended to clients low self esteem as an independent act of nursing.